2005
DOI: 10.2174/157015905774322499
|View full text |Cite
|
Sign up to set email alerts
|

Role of Altered Structure and Function of NMDA Receptors in Development of Alcohol Dependence

Abstract: Long-term alcohol exposure gives rise to development of physical dependence on alcohol in consequence of changes in certain neurotransmitter functions. Accumulating evidence suggests that the glutamatergic neurotransmitter system, especially the N-methyl-D-aspartate (NMDA) type of glutamate receptors is a particularly important site of ethanol's action, since ethanol is a potent inhibitor of the NMDA receptors (NMDARs) and prolonged ethanol exposition leads to a compensatory "upregulation" of NMDAR mediated fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 184 publications
(229 reference statements)
1
12
0
Order By: Relevance
“…Most evidence supports two possible mechanisms that are not exclusionary. One is that ethanol exposure upregulates the number of N-methyl-D-aspartate receptors (NMDAR) (Follesa and Ticku, 1996) and/or changes their subunit composition (Nagy et al, 2003), resulting in hypersensitive conformations of the receptor (Nagy et al, 2005). The second is that release of glutamate (Rossetti et al, 1999) and polyamines (Gibson et al, 2003) is greater during EWD, resulting in the overactivation of NMDARs.…”
Section: Introductionmentioning
confidence: 99%
“…Most evidence supports two possible mechanisms that are not exclusionary. One is that ethanol exposure upregulates the number of N-methyl-D-aspartate receptors (NMDAR) (Follesa and Ticku, 1996) and/or changes their subunit composition (Nagy et al, 2003), resulting in hypersensitive conformations of the receptor (Nagy et al, 2005). The second is that release of glutamate (Rossetti et al, 1999) and polyamines (Gibson et al, 2003) is greater during EWD, resulting in the overactivation of NMDARs.…”
Section: Introductionmentioning
confidence: 99%
“…GRIN2A knockout mice show increased spontaneous locomotor activity and deficits in contextual fear conditioning and spatial learning, as well as reduced hippocampal long-term potentiation (Sakimura et al, 1995) thought to be involved in addiction (Squire, 1992). Several studies showed that chronic administration of drugs of abuse, such as alcohol (Nagy et al, 2005), methamphetamine (Simoes et al, 2008), cocaine (Ben-Shahar et al, 2009), and nicotine (Wang et al, 2007), alters GRIN2A activity in the brain, suggesting that the GRIN2A gene is an excellent candidate target for treating addiction disorders. These studies suggest that GRIN2A is closely associated with drug addiction and is a key mediator of the pathogenesis of drug addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GRIN2A knockout mice failed to show evidence of conditioned place preference, suggesting an impairment in learned reward-related responses to ethanol [16]. Several studies have shown that chronic administration of drugs of abuse, such as alcohol [17], methamphetamine [18], cocaine [19], and nicotine [20], alters the activity of GRIN2A in the brain, suggesting that the GRIN2A gene is an excellent candidate target for treatment of addiction disorders. Importantly, these results indicate that glutamatergic transmission, particularly through GRIN2A-containing NMDA receptors in the nucleus accumbens, probably contributes to the development of opiate addiction and confirms the hypothesis that subtype-selective NMDA receptor antagonists may be beneficial in the treatment of opiate addiction and withdrawal [21].…”
Section: Introductionmentioning
confidence: 99%